Russification and Russianization in Modern Historiography: Recent Developments and Future Directions - Nicholas W. Sessums (Central Europe)
As the Soviet historical archives became accessible to Western scholars beginning in the 1980s, renewed scrutiny was placed on the imperial-colonial policies of the Russian Empire toward its borderlands. These scholars began to interrogate the policies of the imperial administration toward ethnic and national groups in the borderlands from the imperial administrative perspective. In this essay, I geographically circumnavigate the borderlands of the Russian Empire through secondary studies published since the 1980s to understand how scholars have reinterpreted these policies since gaining access to the imperial administrative perspective. I find that they began to challenge the notion that the empire had cohesive and consistently applied policies to Russify its subjects. Instead, scholars now generally argue that policies were applied on a more ad hoc basis depending on the ethnic and national contexts of individual borderlands. Consequently, the concept of ‘Russification’ (obrusenie in Russian) became opaque, difficult to define, and inadequate in capturing the range of imperial policies toward the peoples of the borderlands. Therefore, the application of the term ‘Russianization’ is now more popular among scholars in describing non-assimilatory policies. Further distinction between the two concepts, however, is required in order to understand the full range of policies enacted toward imperial ethnicities and nationalities. Therefore, I also argue in favor of two promising new frameworks in the historiography, namely, the shifting usage of the term inorodtsy (aliens) by imperial administrators over time, and the concept of national indifference. Study of the former, I contend, would highlight the “othering” of non-dominant ethnic and national minorities. The latter permits an understanding of the limits of national constructions, thereby enabling a greater understanding of processes of national construction and, therefore, imperial responses to those constructions. Both would ultimately further clarify the historiographic distinction between Russification and Russianization.